PERAN BADAN PENGAWAS PEMILU KABUPATEN MAYBRAT DALAM MENCEGAH KECURANGAN PELAKSANAAN PILKADA 2024 - Isai Asmuruf; Novalin M Syautam; Weron Murary (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Bawaslu, as an election supervisory body, has tasks regulated under Law Number 7 of 2017 concerning General Elections, to carry out prevention and enforcement against election violations and disputes in the election process, and plays a key role in overseeing various stages of regional elections with high integrity. One of the actions taken by Bawaslu of Maybrat Regency to prevent election fraud, which often occurs, is money politics. Bawaslu must carry out extensive socialization activities to various elements of society, with one of its goals being to reject money politics in the 2024 regional elections. The research used in this final project study, which is empirical legal research, examines how law operates in society, then uses a research approach, specifically a qualitative approach. The research in Maybrat Regency, as the administrative and operational center, became the primary location for directly collecting data as a member of the Bawaslu Regency. The data obtained from literature studies, interviews, and analyzed based on the applicable regulations. Research results obtained include strengthening the capacity of ad hoc supervisory human resources at the district and village levels, case study-based supervision simulations to make it more contextual. Develop a violation reporting application that is easily accessible to the public, use social media for voter education and publication of supervision results. Implement a digital supervision dashboard to monitor campaign activities in real-time. Establish a coordination forum between Bawaslu, KPU, security forces, and NGOs, and encourage participatory supervision through democracy volunteer programs. Conduct anti-money politics campaigns and election simulations in schools and villages, distribute educational materials in local languages to make them easier to understand. Publish monitoring reports openly to increase accountability, use evaluation results to improve future monitoring systems and procedures. Conduct public satisfaction surveys regarding Bawaslu's monitoring performance, and form independent evaluation teams from community members to assess the effectiveness of monitoring programs. Keywords: Bawaslu, Preventing Fraud, Regional Elections, Maybrat Regency